Beyond intention: Predicting children's COVID-19 vaccine uptake using the theory of planned behavior - Eva Yi Hung Lau; Jian-Bin Li; Derwin King Chung Chan (Taylor & Francis Group, 2023)
This prospective study tested if parental factors from the theory of planned behavior (TPB) predicted children's uptake of the COVID-19 vaccine and examined whether parents' intention to vaccinate children against COVID-19 would mediate such associations. Participants were 852 Hong Kong parents of 1076 children aged 5-12. At Time 1, parents reported on items measuring the TPB predictors (i.e. attitudes, subjective norms, and perceived behavioral control) and intention. At Time 2 (approximately 4 months after Time 1), parents reported whether their children had received the COVID-19 vaccine. Attitudes, perceived behavioral control, and intention predicted children's actual uptake of the COVID-19 vaccine. Intention mediated the relations between two TPB predictors, namely attitudes and subjective norms, and children's COVID-19 vaccination uptake. The TPB is considered a useful framework in the development of future COVID-19 vaccine programs for children to promote parents' intention and the subsequent uptake of the COVID-19 vaccine among children.